(untitled) (Perner’s Contacts, 2010)
The paper deals with e-tolling of the I. class roads in relation to national road freight transport. Article analyses e-tolling differences from regional point of view. It investigates the possibilities of II. class roads usage for regional haulage as alternative to the I. class usage.